Comparative analyses of downstream signal transduction targets modulated after activation of the AT1 receptor by two β-arrestin-biased agonists - Santos, Geisa A.; Duarte, Diego A.; Parreiras-e-Silva, Lucas T.; Teixeira, Felipe R.; Silva-Rocha, Rafael M.; Oliveira, Eduardo B.; Bouvier, Michel; Costa-Neto, Claudio M. (Frontiers in Pharmacology, 2015)
G protein-coupled receptors (GPCRs) are involved in essentially all physiological processes in mammals. The classical GPCR signal transduction mechanism occurs by coupling to G protein, but it has recently been demonstrated that interaction with β-arrestins leads to activation of pathways that are independent of the G protein pathway. Also, it has been reported that some ligands can preferentially activate one of these signaling pathways; being therefore called biased agonists for G protein or β-arrestin pathways. The angiotensin II (AngII) AT1 receptor is a prototype GPCR in the study of biased agonism due to the existence of well-known β-arrestin biased agonists, such as [Sar1,Ile4,Ile8]-AngII (SII), and [Sar1,D-Ala8]-AngII (TRV027). The aim of this study was to comparatively analyze the two above mentioned β-arrestin biased agonists on downstream phosphorylation events and gene expression profiles. Our data reveal that activation of AT1 receptor by each ligand led to a diversity of activation profiles that is far broader than that expected from a simple dichotomy between “G protein-dependent” and “β-arrestin-dependent” signaling. We observed clusters of activation profiles common to AngII, SII and TRV027, as well as downstream effector activation that are unique to AngII, SII, or TRV027. Analyses of β-arrestin conformational changes after AT1 receptor stimulation with SII or TRV027 suggests that the observed differences could account, at least partially, for the diversity of modulated targets observed. Our data reveal that, although the categorization “G protein-dependent” vs. “β-arrestin-dependent” signaling can be of pharmacological relevance, broader analyses of signaling pathways and downstream targets are necessary to generate an accurate activation profile for a given ligand. This may bring relevant information for drug development, as it may allow more refined comparison of drugs with similar mechanism of action and effects, but with distinct side effects.